STUDI PENDAHULUAN PENGARUH PENERIMAAN DAN PENGELUARAN NEGARA TERHADAP IMBAL HASIL MISMATCH TREASURY BILLS - Joko Sumantri, M.M (Politeknik Keuangan Negara STAN, 2017)
The purpose of this preliminary study is to assist the Indonesian government and investors in predicting the effect of changes in state revenues and expenditures on yields on bonds to be issued under the name